Effect of pretreatments on the quality and acceptability of the cabinet dried oyster mushroom (Pleurotus florida) - Kamal, Shwet; Rai, R D; Arumuganathan, T; Kumar, Rajesh; Tewari, R P; Khare, Vinay (Mushroom Research, 2016)
Present study has been carried out in order to maintain the quality such as color, flavor and texture of the dried oyster mushroom immediately after drying and - a storage period of 75 days with the help of various pre-drying treatments. It was observed that amongst all the pre-drying treatments steeping of blanched mushroom with 0.05 % KMS + 0.1 % citric acid + 125 ppm EDTA showed a constant color, flavor and texture even after a storage period of 75 days. Although, steeping treatment has shown excellent results immediately after drying but deteriorated after a storage period of 75 days.Â